DMF-based ionic liquid promoted efficient cycloaddition of vinylarenes with active alkynes - Ahmed Ali Hullio (Green Chemistry Letters and Reviews, 2017)
N,N-Dimethylformamide (DMF)-based ionic liquid is a multipurpose ionic liquid having numerous applications. In the present study it has been shown to be an efficient and recyclable nucleophilic reagent-cum-solvent for the synthesis of a variety of 1,2-disubstituted-3,4-dihydronaphthalenes by cycloaddition of different vinylarenes with electron-deficient alkynes. The present protocol has been demonstrated to be more efficient, green and cost effective as compared with other reported methods.